2021
DOI: 10.1021/acs.oprd.0c00536
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Qualities of High-Quality Palladium on Carbon Catalysts for Hydrogenolysis

Abstract: Palladium-catalyzed hydrogenolysis is often the final step in challenging natural product total syntheses and a key step in industrial processes producing fine chemicals. Here, we demonstrate that there is wide variability in the efficiency of commercial sources of palladium on carbon (Pd/C) resulting in significant differences in selectivity, reaction times, and yields. We identified the physicochemical properties of efficient catalysts for hydrogenolysis: (1) small Pd/PdO particle size (2) homogeneous distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 23 publications
0
33
0
2
Order By: Relevance
“…In contrast, a previous study suggested that the Pd/C catalyst with poor catalytic activity has a higher PdO content; in other words, the formation of PdO will significantly reduce the catalytic activity. Some Pd-based nanoalloy catalysts , improved the catalytic activity toward the FOR due to the formation of the Ag–O and Rh–O species.…”
Section: Results and Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast, a previous study suggested that the Pd/C catalyst with poor catalytic activity has a higher PdO content; in other words, the formation of PdO will significantly reduce the catalytic activity. Some Pd-based nanoalloy catalysts , improved the catalytic activity toward the FOR due to the formation of the Ag–O and Rh–O species.…”
Section: Results and Discussionmentioning
confidence: 70%
“…Oxygen atoms occupy the catalytic active sites on the surface, which increases the limiting potential of the FOR, thereby reducing the catalytic activity. Figure S3 In contrast, a previous study 69 suggested that the Pd/C catalyst with poor catalytic activity has a higher PdO content; in other words, the formation of PdO will significantly reduce the catalytic activity. Some Pd-based nanoalloy catalysts 5,6 improved the catalytic activity toward the FOR due to the formation of the Ag−O and Rh−O species.…”
Section: Resultsmentioning
confidence: 78%
“…Due to its catalytic efficiency, easy recyclability, and diverse catalytic modes, the Pd/C catalyst has found, and will continue to find, valuable applications in the catalysis of organic reactions. It is worth pointing out that there is wide variability in the efficiency of commercial sources of Pd/C, resulting in significant differences in selectivity, reaction times, and yields [95]. On the other hand, it is still a significant challenge to explore the solution for the Pd/C catalyst's progressive deactivation upon successive reuses when, due to palladium leaching, the catalyst is hard recycled after a few times, and thus, it becomes inactive or much less active.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that commercial Pd/C consists of bulk metal and metal nanoparticles of highly variable size, shape and oxidation state, and thus there is often significant variability in the reactivity of different sources and batches. 17 The lot-lot-variability constitutes a burden on academic and industrial chemists, adding to the cost and reliability of synthesis. The safe handling, disposal and recycling of Pd/C at scale also poses challenges at commercial scale.…”
Section: Ii)mentioning
confidence: 99%